Mortality of metallo-β-lactamase-producing Enterobacterales bacteremias with combined ceftazidime–avibactam plus aztreonam vs. other active antibiotics: a multicenter target trial emulationResearch in context - Ivan Alfredo Huespe; Emilio Felipe Huaier Arriazu; Marisa Sanchez; Vanina Stanek; Javier Alberto Pollán; Susana Bauque; Débora Ávila Poletti; Verónica Monzón; Paola Novelli Poisson; María Virginia Boutet; Eleonora Cunto; Viviana Chediack; et al. (The Lancet Regional Health. Americas, 2025)
Summary: Background: Bacteremias caused by metallo-β-lactamase (MBL)-producing Enterobacterales are a critical challenge due to their limited treatment options. Although ceftazidime-avibactam (CAZAVI) combined with aztreonam (ATM) has shown in vitro efficacy, no prior studies have rigorously compared its clinical effectiveness to Other Active Antibiotics (OAAs). This study aims to evaluate the efficacy and safety of CAZAVI + ATM vs. OAAs in a large cohort of MBL bacteremia. Methods: A retrospective, multicenter, target trial emulation was conducted across 17 hospitals in Argentina between January 2016 and October 2024. Patients with confirmed MBL bacteremia who initiated active antibiotic treatment within 24 h of MBL identification and 96 h of blood sampling were included. Inverse probability of treatment weighting (IPTW) was used to reduce indication bias, and the analysis accounted for hospital clustering within Argentina's public, private, and social security health systems. The primary outcome was 30-day all-cause mortality, with secondary outcomes including clinical failure (relapse, complications, or death) and adverse events. Findings: Among 243 patients (93 receiving CAZAVI + ATM and 150 receiving OAAs), the 30-day mortality rate was 35% in the CAZAVI + ATM group vs. 47% in the OAA group (adjusted odds ratio [OR] 0·63, 95% CI 0·43–0·91, p < 0·01). Clinical failure occurred in 46% of the CAZAVI + ATM group and 53% of the OAA group (adjusted hazard ratio [HR] 0·65, 95% CI 0·44–0·97; p = 0·03). Adverse events were lower with CAZAVI + ATM (9·6% vs. 22·8%, p = 0·014). Interpretation: These findings suggest CAZAVI + ATM might be associated with lower mortality, reduced clinical failure, and fewer adverse events compared to OAAs in patients with MBL-type Enterobacterales bacteremia. Further prospective studies are warranted to confirm these observations. Funding: No specific funding was provided for this study.